Interactions between conditional cash transfers and preferred secondary schools in Jamaica - Diether W. Beuermann; Andrea Ramos Bonilla; Marco Stampini (Inter-American Development Bank (IDB), 2022)
Covering the full population of applicants to the Jamaican Conditional Cash Transfer Program (PATH), we explore whether receiving PATH benefits alters the academic returns to subsequently attending a more preferred public secondary school. To uncover causal associations, we exploit exogenous variation arising from both the PATH eligibility criteria and the centralized allocation process to public secondary schools within a double regression discontinuity design. Among girls, receiving PATH benefits before secondary school enrollment does not influence the academic gains from attending a more selective school. However, boys exposed to PATH experience significantly lower returns to subsequently attending a more selective school with respect to comparable peers who did not receive PATH. These results highlight the relevance of considering both the direct effects of conditional cash transfers and the potential indirect effects that such policies could convey through altering the effectiveness of other related policies.
Keywords: H52; H75; I21; I26; I28; I38; 330; academic performance; conditional cash transfers; school selectivity; Jamaica